2019
DOI: 10.2169/internalmedicine.1176-18
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Occlusion with Endobronchial Watanabe Spigot for Hemoptysis in a Mechanically Ventilated Patient with Extracorporeal Circulation

Abstract: Bronchial occlusion with endobronchial Watanabe spigots (EWSs) can be an essential therapeutic measure for treating massive hemoptysis in intensive care patients when no other conventional options are available. A 68-year-old-man on mechanical ventilation and extracorporeal circulation after cardiovascular surgery presented massive hemoptysis. He was deemed unfit for bronchial artery embolization (BAE) and surgery while in the intensive care setting; thus, bronchial occlusion was performed using EWSs. His hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…We were unable to achieve complete hemostasis in this case; however, temporary hemostasis was achieved with EBO+EWS. Previous studies have reported the effectiveness of EBO+EWS for hemostasis [ 5 , 7 – 27 ]. We analyzed 33 previously reported cases from 22 articles, in addition to our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were unable to achieve complete hemostasis in this case; however, temporary hemostasis was achieved with EBO+EWS. Previous studies have reported the effectiveness of EBO+EWS for hemostasis [ 5 , 7 – 27 ]. We analyzed 33 previously reported cases from 22 articles, in addition to our case.…”
Section: Discussionmentioning
confidence: 99%
“…EBO can be performed with bronchial blockers [ 4 ]. The endobronchial Watanabe spigot (EWS) is a silicone filter for refractory pneumothorax and bronchial fistulas and can be used to manage hemoptysis [ 5 , 6 ]. To perform EBO with an EWS, a bronchoscope is used to fill the bleeding bronchus with an EWS, which is grasped by forceps while the patient is intubated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, minimally invasive methods have become more preferred in the management of patients with a tracheal injury who are under high surgical risk due to the severity of the underlying disease and comorbidity. The first of these methods is the “watanabe spigot” silicone tube with a conical shape and protrusions on the sides to hold onto the bronchial wall designed by a Japanese pulmonologist in three different sizes (5, 6 and 7 mm) [ 65 ]. Such devices were originally introduced in clinical practice to treat persistent pneumothorax with pulmonary fistula and prolonged air leaks.…”
Section: Non-surgical Approachesmentioning
confidence: 99%
“…The flexible bronchoscopy is instrumental in identifying the source of bleeding, 3 and bronchial occlusion with endobronchial Watanabe spigots (EWSs) has been reported as an option, and at times, definitive treatment for massive haemoptysis unfit for interventional radiology (IVR) and surgery. 4 …”
Section: Introductionmentioning
confidence: 99%